Customer Success Management Helping Business Customers Achieve Their Goals - Kleinaltenkamp, Michael; Prohl-Schwenke, Katharina; Elgeti, Laura (Cham : Springer International Publishing : Imprint: Springer, 2023)
End of 2022, nearly 200,000 people indicated holding a position as a customer success manager on LinkedIn. Customer success management (CSM) is thus the fastest growing business function. It was first implemented in selected service businesses, but currently CSM applications are spreading globally across industries. This book provides a clear understanding of CSM for practitioners based on comprehensibly prepared knowledge from practical and scientific resources. The book can be used as a practical guide to learn about CSM process and the roles, necessary capabilities, and expectations toward customer success managers. Furthermore, it also shows how CSM differs from and, at the same time, relates to existing customer-related management concepts such as value-based selling, key account management and customer relationship management. The presented insights are not only relevant for customer success managers, but also for those aiming at such a position in the future. The bookis also useful for supplier and customer representatives who are connected with customer success management activities in their daily business.
Chapter 1 The Rise of a New Business Function: Customer Success (Management) -- Chapter 2 Customer Success and Customer Success Management -- Chapter 3 Customer Success Management Drivers -- Chapter 4 Value-Based Selling -- Chapter 5 Solution Realization -- Chapter 6 Customer Success Management Activities -- Chapter 7 Adapting the Customer Value Proposition -- Chapter 8 Customer Advocacy -- Chapter 9 Customer Success Management Outcomes -- Chapter 10 Customer Success Management Structures -- Index.
Keywords: Customer relations -- Management; Telemarketing; Internet marketing; Consumer behavior; Customer Relationship Management; Digital Marketing; Consumer Behavior